Kombinasi Metode Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) dan Pembobotan Rank Order Centroid (ROC) dalam Pemilihan Tablet PC Terbaik - Ryan Prayoga; Adinda Tria Suci; Titus Kristanto; Samsul Lutfi; Desyanti; Yonky Pernando (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Tablet PC which is one part of technological developments in the field of communication that aims to meet the needs of users where these needs are not found on smartphones or laptops, is an option that can be an alternative communication tool that can meet needs involving a smartphone. such as designing, playing games, and working. related to the many models of tablet PCs in the world of communication causes the selection of the best tablet PC to be a problem for the users themselves. One of them is if the user chooses the wrong type of tablet PC according to their needs, the tablet PC does not make it easier, instead it hinders the activities of the user himself. therefore data from the types of tablet PCs are collected from 5 criteria and 7 alternatives where the criteria have been determined including screen size, memory capacity, memory type, hard disk capacity and price. From these criteria, the use of ROC can be used to giving weight to each criterion which is then determined using the MOORA method included in the decision that can give the maximum and accurate final preference value, so this study determines the best tablet pc choice option is alternative A1 brand apple ipad air with a final value of 0.054 as the best alternative.